solving an algebraic question that says c+-2=6

c + (-2) = 6 Is the same as saying c - 2 = 6, because adding a negative is the same as subtracting.

c -2 = 6 Given

c -2 + 2 = 6 + 2 Add 2 to each side

c + 0 = 6 + 2 Inverse property of addition

c = 6 + 2 Identity property of addition

c = 8 Simplify (6 + 2 = 8)

## Comments

If you add 2 to both sides of the equation (to keep both sides equal), you eliminate the -2.

-2 + 2 = 0. c + 0 = c.

Then you add 2 to the right side of the equation and you have your answer for c.

c = 6 + 2 (I hope you know how to add those 2 numbers.)

Apply the same method to similar problems.